Reconstitution of a Secondary Cell Wall in a Secondary Cell Wall-Deficient Arabidopsis Mutant - Sakamoto, Shingo; Mitsuda, Nobutaka (Plant and cell physiology, 2015)
The secondary cell wall constitutes a rigid frame of cells in plant tissues where rigidity is required. Deposition of the secondary cell wall in fiber cells contributes to the production of wood in woody plants. The secondary cell wall is assembled through co-operative activities of many enzymes, and their gene expression is precisely regulated by a pyramidal cascade of transcription factors. Deposition of a transmuted secondary cell wall in empty fiber cells by expressing selected gene(s) in this cascade has not been attempted previously. In this proof-of-concept study, we expressed chimeric activators of 24 transcription factors that are preferentially expressed in the stem, in empty fiber cells of the Arabidopsis nst1-1 nst3-1 double mutant, which lacks a secondary cell wall in fiber cells, under the control of the NST3 promoter. The chimeric activators of MYB46, SND2 and ANAC075, as well as NST3, reconstituted a secondary cell wall with different characteristics from those of the wild type in terms of its composition. The transgenic lines expressing the SND2 or ANAC075 chimeric activator showed increased glucose and xylose, and lower lignin content, whereas the transgenic line expressing the MYB46 chimeric activator showed increased mannose content. The expression profile of downstream genes in each transgenic line was also different from that of the wild type. This study proposed a new screening strategy to identify factors of secondary wall formation and also suggested the potential of the artificially reconstituted secondary cell walls as a novel raw material for production of bioethanol and other chemicals.